Method for constructing gradient niobium titanium oxygen sulfide negative electrode material through two-step hydrothermal method and application of gradient niobium titanium oxygen sulfide negative electrode material
The preparation of gradient niobium sulfide titanium oxide material through two-step hydrothermal method solved the problem of low electronic and ion conductivity of niobium titanium oxide negative electrode material in lithium-ion hybrid capacitors, and achieved improvement in material rate performance and electrochemical performance.
Patent Information
- Application Number
- CN202411873189.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
AI Technical Summary
The electronic and ionic conductivity of niobium titanium anode material in lithium-ion hybrid capacitors is low, limiting its application in lithium-ion batteries and hybrid capacitors.
A two-step hydrothermal method is used to prepare gradient niobium sulfide titanium oxide materials. By precisely controlling the vulcanization process, the sulfur atom gradient replaces oxygen atoms to form a material with rich heterogeneity of oxidative components, thereby improving electron and ionic conductivity.
It significantly improves the rate performance and electrochemical performance of niobium titanium oxide materials, and improves the comprehensive performance of lithium-ion hybrid capacitors.
Smart Images

Figure CN119683683A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrochemical energy storage, and relates to a preparation method of a gradient sulfided niobium titanium oxide negative electrode material and its application, and specifically to a two-step hydrothermal method for constructing a gradient sulfided niobium titanium oxide negative electrode material and its application in a lithium ion hybrid capacitor. Background Art
[0002] Lithium-ion hybrid capacitors integrate the advantages of high energy density of lithium-ion batteries and high power density and long cycle life of supercapacitors. The negative electrode of lithium-ion hybrid capacitors uses battery-type materials with Faraday process. Theoretically, the negative electrode materials of lithium-ion batteries can be used as negative electrode materials of lithium-ion hybrid capacitors. Lithium titanate material (Li4Ti5O 12 ) is one of the most widely studied negative electrode materials in the early stage of lithium-ion hybrid capacitor development due to its high safety, good cycle performance (zero strain material), stable voltage platform and wide operating range. However, lithium titanate has a low theoretical capacity (175mAh g -1 ), low intrinsic conductivity (~10 -13 S cm -1 ) and the lithium ion migration rate is low (10 -9 ~10 -13 cm 2 s -1 ) and other issues have seriously restricted the development of high-performance lithium-ion hybrid capacitors.
[0003] In recent years, niobium-based oxides have attracted considerable attention as high-power negative electrode materials for lithium-ion batteries due to their high compaction density and high gram capacity, and have the potential to replace lithium titanate materials. As a typical intercalation material, the excellent electrochemical performance of niobium titanium oxide (TiNb2O7) anode mainly stems from its unique structure, in which niobium (Nb) and titanium (Ti) atoms are located at the center of NbO6 and TiO6 octahedra, respectively, in a disordered arrangement. In addition, the NbO6 octahedron and the TiO6 octahedron are connected by edges and vertices to form an open tunnel-like gap that can accommodate the transmission of lithium ions. The insertion and extraction of lithium ions are relatively easy, so it has excellent rate performance. Niobium titanium oxide not only has the advantages of conventional lithium titanate materials in terms of cycle stability and long life, but also has the advantages of Ti 3+ / Ti 4+ , Nb 4+ / Nb 5+ and Nb 3+ / Nb 4+ Multiple redox pairs; has a higher theoretical specific capacity (387.6 mAh g -1 ), the working potential is similar to that of lithium titanate (1.6V vs Li + / Li), which can effectively prevent the formation of lithium dendrites and the reduction and decomposition of the electrolyte. Compared with traditional batteries, the safety performance is greatly improved. However, niobium titanium oxide materials also have some problems. The electronic and ionic conductivity of the material is low. Therefore, it is urgent to invent a method that can simultaneously improve the electronic and ionic conductivity of niobium titanium oxide materials to promote their application in lithium-ion batteries and hybrid capacitors. Summary of the invention
[0004] In order to solve the problem of low electronic and ionic conductivity of niobium titanium oxide negative electrode materials for lithium ion hybrid capacitors, the present invention provides a two-step hydrothermal method for constructing gradient sulfide niobium titanium oxide negative electrode materials and their applications. The method adopts a two-step hydrothermal method to prepare gradient sulfide niobium titanium oxide materials. Since the band gap energy of metal sulfides is low, the intrinsic activity of niobium titanium oxide materials is effectively adjusted by precisely controlling gradient sulfurization; sulfur atoms gradiently replace oxygen atoms, and niobium titanium oxide materials produce compositional heterogeneity with rich oxidation states from the surface to the bulk phase, which is conducive to the rapid migration of lithium ions and the transfer of charges, greatly improving its rate performance, and improving the comprehensive performance of niobium titanium oxide lithium ion hybrid capacitors.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A two-step hydrothermal method for constructing a gradient sulfide niobium titanium oxide negative electrode material, wherein a conventional niobium titanium oxide material precursor is prepared by a hydrothermal method, and then a sulfur source K2S is added for secondary hydrothermal treatment, and finally a gradient sulfide niobium titanium oxide material (TiNb2O7@TiNb2O7) is obtained by high temperature annealing. x S 7-x ), specifically including the following steps:
[0007] Step 1: Preparation of niobium titanium oxide precursor:
[0008] The niobium titanium oxide material precursor is prepared by a hydrothermal method, and the specific steps are as follows:
[0009] Step 1. Add 50 ml of anhydrous ethanol into a glass container, and under stirring, add 1.351 g of NbCl5 and 0.851 g of tetrabutyl titanate into the anhydrous ethanol, and stir to ensure sufficient mixing;
[0010] Step 1 and 2: After the mixing is completed, the transparent solution obtained by stirring in step 1 is transferred to a Teflon-lined stainless steel autoclave and kept warm at a temperature of 180 to 200°C;
[0011] The insulation time is 12 to 36 hours;
[0012] Step 13: After the autoclave is cooled to room temperature, the precipitate is collected by washing with ethanol and centrifugation to obtain a niobium titanium oxide precursor material, wherein:
[0013] The centrifugal speed is 8000-10000 r / min;
[0014] Step 2: Secondary hydrothermal preparation of gradient niobium titanium sulfide precursor material:
[0015] Step 21: Prepare a K2S ethanol solution, wherein:
[0016] The concentration of the K2S ethanol solution is 10-100 mM, preferably, the solution concentration is 10 mM, 20 mM, 40 mM, 60 mM, 80 mM and 100 mM;
[0017] Step 2: Weigh the niobium titanium oxide precursor prepared in step 1 and put it into a beaker containing K2S ethanol solution. After stirring and mixing, transfer it to a Teflon-lined stainless steel autoclave and keep it warm at 120-150°C, wherein:
[0018] The dosage ratio of the niobium titanium oxide precursor material to the K2S ethanol solution is 0.4-0.6 g: 60 ml;
[0019] The insulation time is 1 to 5 hours;
[0020] Step 23: After the autoclave is cooled to room temperature, the precipitate is collected by washing with ethanol and centrifugation, and vacuum dried in a vacuum oven to obtain a gradient niobium titanium sulfide precursor material, wherein:
[0021] The vacuum drying temperature is 60°C and the time is 12h;
[0022] Step 3: Transfer the gradient niobium titanium sulfide precursor material to a tube furnace and calcine it under an Ar atmosphere to obtain a gradient niobium titanium sulfide material, wherein:
[0023] The calcination temperature is 800-1600° C., preferably, the calcination temperature is 800° C., 850° C., or 1000° C., and the calcination time is 6-24 hours.
[0024] The gradient niobium titanium sulfide material prepared by the above method can be used as a negative electrode material in a lithium-ion hybrid capacitor. The gradient niobium titanium sulfide material, the conductive agent and the binder are dispersed in an NMP solvent in a mass ratio of 96:2:2 to obtain a negative electrode slurry. The slurry is coated on a negative electrode collector, and after drying, rolling and punching, a negative electrode sheet is obtained, and then a button-type lithium-ion half-cell is assembled.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] The present invention prepares the gradient sulfide niobium titanium oxide hybrid capacitor negative electrode material by a two-step hydrothermal method. By finely controlling the concentration and duration of hydrothermal sulfidation, sulfur atoms replace some oxygen atoms to varying degrees, thereby improving the electron transfer and lithium ion deintercalation rate of the niobium titanium oxide material, and greatly improving the rate performance. The gradient sulfide niobium titanium oxide hybrid capacitor negative electrode material prepared by this method can be used in the field of high-power, high-specific-energy niobium titanium oxide lithium ion hybrid capacitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of gradient sulfided niobium titanium oxide material;
[0028] Figure 2 This is the SEM image of the gradient sulfided niobium titanium oxide material;
[0029] Figure 3 5C rate cycle diagram of comparative example and embodiment 2;
[0030] Figure 4 It is a cycle comparison diagram of the comparative example and the embodiment. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0032] Comparative Example
[0033] The comparative example is a pure phase spherical niobium titanium oxide material, which is subjected to non-gradient sulfurization treatment. The specific preparation method is as follows: 1.351g NbCl5 and 0.851g tetrabutyl titanate are added to 50ml ethanol and magnetically stirred for 2h. Then, the resulting solution is transferred to a 100mL Teflon-lined stainless steel autoclave and kept at 180°C for 24h. After the autoclave is cooled to room temperature, the precipitate is collected by ethanol washing and centrifugation at a speed of 8000-10000r / min to obtain a precursor material. Subsequently, the precursor material is transferred to a tubular furnace and calcined at 850°C for 12h in an air atmosphere to obtain pure phase TiNb2O7.
[0034] Example 1
[0035] This embodiment provides a two-step hydrothermal method for constructing a gradient niobium titanium sulfide negative electrode material, the method comprising the following steps:
[0036] Step 1: Preparation of niobium titanium oxide precursor: Add 50 ml of anhydrous ethanol to a glass container, add 1.351 g of NbCl5 and 0.851 g of tetrabutyl titanate to the above solution under stirring conditions, and stir for 2 hours to ensure sufficient mixing; after mixing, transfer the stirred transparent solution to a 100 mL Teflon-lined stainless steel autoclave and keep it at 180°C for 24 hours. After the autoclave is cooled to room temperature, the precipitate is collected by ethanol washing and centrifugation at a speed of 8000-10000 r / min to obtain a niobium titanium oxide precursor material.
[0037] Step 2: Secondary hydrothermal preparation of gradient niobium titanium sulfide precursor material: First, prepare 60 ml of 10 mM K2S ethanol solution. Then, put 0.5 g of the prepared niobium titanium oxide precursor into a beaker containing K2S ethanol solution, stir and mix for 0.5 h, then transfer to a 100 mL Teflon-lined stainless steel autoclave and keep warm at 120 ° C for 1 h. After the autoclave is cooled to room temperature, the precipitate is collected by ethanol washing and centrifugation, and vacuum dried at 60 ° C in a vacuum oven for 12 h to obtain a gradient niobium titanium sulfide precursor material.
[0038] Step 3: Transfer the gradient niobium titanium sulfide precursor material to a tube furnace and calcine it at 850° C. for 6 hours under an Ar atmosphere to obtain a gradient niobium titanium sulfide material.
[0039] Step 4: Disperse the obtained gradient niobium titanium sulfide material, conductive agent (acetylene black, carbon nanotubes), and binder (PVDF) in N-methylpyrrolidone (NMP) solvent in a mass ratio of 96:2:2 to obtain a negative electrode slurry, planetary stir for 10 hours, apply the slurry on the negative electrode collector, dry, roll and punch to obtain a negative electrode sheet, and then assemble a button lithium-ion half-cell.
[0040] Example 2
[0041] The difference between this embodiment and embodiment 1 is that in step 2, the concentration of the K2S ethanol solution is 20 mM, which can obtain a niobium titanium oxide material with a thicker gradient sulfide layer, and then obtain the correlation between the sulfur source concentration and the gradient sulfide layer and the electrochemical properties of the material, thereby optimizing the material preparation parameters.
[0042] Example 3
[0043] The difference between this embodiment and embodiment 1 is that: in step 2: first, prepare 60 ml of a 10 mM K2S ethanol solution. Then, put 0.5 g of the prepared niobium titanium oxide precursor into a beaker containing the K2S ethanol solution, stir and mix for 0.5 h, and then transfer to a 100 mL Teflon-lined stainless steel autoclave, and keep it at 120°C for 3 h. After the autoclave is cooled to room temperature, the precipitate is collected by ethanol washing and centrifugation, and vacuum dried at 60°C in a vacuum oven for 12 h to obtain a gradient sulfide niobium titanium oxide precursor material.
[0044] Example 4
[0045] The present embodiment is different from the embodiment 1 in that: in step 3, the gradient niobium titanium sulfide precursor material is transferred to a tube furnace and calcined at 850° C. for 12 h in an Ar atmosphere to obtain a gradient niobium titanium sulfide material.
[0046] The gradient niobium titanium sulfide material obtained in Example 1 is as follows Figure 1 As shown in the SEM images Figure 2 As shown by Figure 1 and Figure 2 It can be seen that there is no significant change in the microscopic morphology. Figure 3 This is a 5C cycle comparison diagram of the half-cell assembled with the gradient niobium titanium sulfide material prepared in Example 2 and the comparative sample. Figure 3 It can be seen that the capacity at 5C rate is improved after the improvement, which is mainly due to the increase in the intrinsic activity of the gradient sulfided niobium titanium oxide material. The heterogeneous components provide ion migration and charge transfer power, which improves the electrochemical performance of the niobium titanium oxide material.
[0047] The 0.5C cycle performance of the lithium ion half-cells prepared in Examples 1-4 and the comparative example was tested. The test results are as follows: Figure 4 As shown, from Figure 4 It can be seen that the cycle performance of the modified niobium titanium oxide electrode is significantly improved, and the samples of Examples 1-4 all show cycle performance better than that of the comparative example samples. In addition, the cycle performance of Example 2 is better than that of Examples 1, 3 and 4, indicating that compared with the secondary hydrothermal time and high temperature annealing time, the sulfur source concentration is the main factor affecting the gradient sulfide niobium titanium oxide material.
Claims
1. A two-step hydrothermal method for constructing a gradient niobium titanium sulfide negative electrode material, characterized in that The method comprises the following steps: Step 1: Preparation of niobium titanium oxide precursor: The niobium titanium oxide material precursor is prepared by a hydrothermal method; Step 2: Secondary hydrothermal preparation of gradient niobium titanium sulfide precursor material: Step 21: prepare a K2S ethanol solution, wherein: the concentration of the K2S ethanol solution is 10-100 mM; Step 22: Weigh the niobium titanium oxide precursor prepared in step 1 and put it into a beaker containing K2S ethanol solution. After stirring and mixing, transfer it to a Teflon-lined stainless steel autoclave and keep it warm at 120-150°C, wherein the amount ratio of the niobium titanium oxide precursor material to the K2S ethanol solution is 0.4-0.6g:60ml; Step 23: After the autoclave is cooled to room temperature, the precipitate is collected by washing with ethanol and centrifugation, and vacuum dried in a vacuum oven to obtain a gradient niobium titanium sulfide precursor material; Step 3: Transfer the gradient niobium titanium sulfide precursor material to a tube furnace and calcine it under an Ar atmosphere to obtain a gradient niobium titanium sulfide material.
2. The method for constructing a gradient niobium titanium sulfide negative electrode material by two-step hydrothermal method according to claim 1, characterized in that The specific steps of step one are as follows: Step 1. Add 50 ml of anhydrous ethanol into a glass container, and under stirring, add 1.351 g of NbCl5 and 0.851 g of tetrabutyl titanate into the anhydrous ethanol, and stir to ensure sufficient mixing; Step 1 and 2: After the mixing is completed, the transparent solution obtained by stirring in step 1 is transferred to a Teflon-lined stainless steel autoclave and kept warm at a temperature of 180 to 200°C; Step 13: After the autoclave is cooled to room temperature, the precipitate is collected by washing with ethanol and centrifugation to obtain a niobium titanium oxide precursor material.
3. The method for constructing a gradient niobium titanium sulfide negative electrode material by two-step hydrothermal method according to claim 2, characterized in that The insulation time is 12 to 36 hours.
4. The method for constructing a gradient niobium titanium sulfide negative electrode material by two-step hydrothermal method according to claim 2, characterized in that The centrifugal speed is 8000-10000 r / min.
5. The method for constructing a gradient niobium titanium sulfide negative electrode material by two-step hydrothermal method according to claim 1, characterized in that The insulation time is 1 to 5 hours.
6. The method for constructing a gradient niobium titanium sulfide negative electrode material by two-step hydrothermal method according to claim 1, characterized in that The vacuum drying temperature is 60° C. and the time is 12 h.
7. The two-step hydrothermal method for constructing a gradient niobium titanium sulfide negative electrode material according to claim 1 is characterized in that The calcination temperature is 800-1600° C. and the calcination time is 6-24 hours.
8. Use of a gradient niobium titanium sulfide negative electrode material prepared by the method according to any one of claims 1 to 7 in a lithium ion hybrid capacitor.